Soybean seeds imbibition in potassium phosphate solution - Rossetto, Claudia Antonia Vieira; Kaufmann, Lorena; Jacob-Neto, Jorge; Franco, Avílio Antonio (Pesquisa Agropecuaria Brasileira, 2002)
The experiment was carried out to study the possibility to increase the phosphorus and potassium contents in soybean seeds (Glycine max (L.) Merrill) cv. EMBRAPA 66, using three methods of soaking (moist substrate, immersion and immersion under vacuum) and the KH2PO4 concentrations: 0, 50, 100, 150 and 200 mM. The experimental design was a factorial (methods of soaking x KH2PO4 concentrations) replicated four times. Phosphorus and potassium contents, seed vigor and germination were determined just after soaking and after drying at room conditions. Soaking the seeds in immersion and immersion under vacuum resulted in 14% increase in the P concentration in the soybean seeds. The methods of soaking and KH2PO4 concentrations did not increase the K concentrations in the soybean seeds. Soaking the seeds in moist substrate caused less damage to their physiological quality. Drying the seeds accentuates the damages caused by the imbibition methodology.